"Following the Breath": A Trauma-Informed Intervention for Educator Wellness in Rural Montana - Lauren Davis; Alexandra Aylward; Brandon G. Scott; Jonathan Jacobs (MDPI AG, 2022)
Given the prevalence of mental health issues for both educators and adolescents in rural Montana, this project is designed to help mitigate the impact of stressors by providing coping strategies linked to improvements in overall mental health outcomes for teachers, which may ultimately lead to improved co-regulation of students and classroom climate. The immediate goal of this pilot study was to measure physical and mental health outcomes of educators resulting from a remotely-delivered trauma-informed yoga intervention. Findings suggest improvements in participants' depression and anxiety levels, trauma symptoms, sleep quality, and non-significant changes in heart rate variability and cortisol levels.